Legal Liability of Contract Workers Who Terminate Employment Relationships Unilaterally: A Study of Article 17 of Government Regulation Number 35 of 2021 - Turija; Indrayanto (Jurnal Ilmiah Hukum dan Keadilan, 2026)
This study is intended to describe the form of legal accountability for workers with the status of Fixed Time Work Agreements (PKWT) who resign without going through the agreed procedures, as well as assess the implementation of Article 17 of Government Regulation No. 35 of 2021 regarding the termination of employment before the contract period ends. The research uses normative juridical methods through literature search, analysis of laws and regulations, legal principles, and doctrines related to employment. The results of the study show that unilateral resignation by PKWT workers does not eliminate the right to compensation, because employers are still obliged to pay compensation money as stipulated in Article 15 and Article 17 of Government Regulation No. 35 of 2021 based on the actual working period. However, the implementation of this rule often does not run optimally because many workers choose not to demand their rights, plus the practice of oral PKWT, which opens up room for deviations from contractual principles. Therefore, it is necessary to increase supervision and enforcement of rules by the government, especially the Manpower Office, so that the protection of PKWT workers is carried out effectively.